Adverse effects of parenteral dexamethasone in the treatment of pemphigus vulgaris (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Background: Pemphigus vulgaris is associated with high morbidity as well as significant mortality rate. Today the risk of death in pemphigus from the side effect of oral prednisolone is greater than risk of death from the disease itself. Objective: To observe the adverse effects of parenteral dexamethasone compared with oral prednisolone in the treatment of pemphigus vulgaris. Methods: An interventional study was carried out in the department of Dermatology and Venereology, Bangabandu Sheikh Mujib Medical University, Dhaka, Bangladesh. Total number of patients was thirty and among them fifteen patients were treated with parenteral dexamethasone (Group-A) and other fifteen were treated with oral prednisolone (Group-B). Results: The study showed statistically significant differences of skin lesion as well as mucosal lesion of pemphigus after 6 weeks of therapy between of two groups (P